Evaluation of wood cutting forces in dry and wet conditions by small-scale chipping tests applying different analysis methods. Issue 3 (4th May 2019) - Pichler, Philip; Springer, Sebastian; Leitner, Martin
ABSTRACT: The aim of this paper is to study the effect of high moisture content in comparison to dry timber on the resulting cutting forces based on experimental small-scale chipping tests. Therefore, a wood chipper for single cuts is designed and different species of Austrian locally growing trees are utilized. The test specimens are investigated in almost dry and soaked wet conditions. The resistance of wood is measured utilizing a force sensor and the signal during the cutting process is subsequently analysed by two different methods. The results reveal that the mean value of the acting force during cutting is 38–81% minor compared to the maximum force. Even though the peak of the dynamically acting load is measured for just a comparably small time range, it reveals an impact on the fatigue behaviour of the tool as well as the tool supporting material. Hence, an approach of evaluated load spectra is applied to include the load distribution of the chipping process. The effect of dry and wet wood on the cutting resistance is examined, whereby wood exhibiting a high moisture content of 30–40% changes the acting load up to 98%, depending on the method of analysis.